2022
DOI: 10.1186/s12882-022-02670-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac valve calcification is associated with mortality in hemodialysis patients: a retrospective cohort study

Abstract: Background Cardiac valve calcification (CVC) is common in end-stage renal disease (ESRD). We investigated the effect of CVC on all-cause and cardiovascular (CV) mortality in maintenance hemodialysis (MHD) patients. Methods A retrospective cohort study was conducted on 434 hemodialysis patients who underwent echocardiography for qualitative assessment of valve calcification with complete follow-up data from January 1, 2014, to April 30, 2021. The ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…), we found that CVC was an independent risk factor for all-cause mortality but not cardiovascular mortality in IHD patients, with an HR of 2.14. Our findings are consistent with previous studies about all-cause mortality, but cardiovascular mortality was not significantly higher in the CVC group, which is inconsistent with Bai’s study [ 15 ]. There may be several reasons: Bai’s study enrolled more MHD patients (434) with much longer dialysis durations than our patients (3.29 ~ 3.58 years vs. 1.45 ~ 1.83 years).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…), we found that CVC was an independent risk factor for all-cause mortality but not cardiovascular mortality in IHD patients, with an HR of 2.14. Our findings are consistent with previous studies about all-cause mortality, but cardiovascular mortality was not significantly higher in the CVC group, which is inconsistent with Bai’s study [ 15 ]. There may be several reasons: Bai’s study enrolled more MHD patients (434) with much longer dialysis durations than our patients (3.29 ~ 3.58 years vs. 1.45 ~ 1.83 years).…”
Section: Discussionsupporting
confidence: 54%
“…CVC is regarded as an age-related degenerative disorder with little impact on heart function. Although CVC has little effect on the general population, it is an independent risk factor for all-cause mortality and cardiovascular mortality in ESRD and MHD patients [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following the inclusion criteria, 22 (12,(15)(16)(17)(18)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) articles were eventually included in our study. The study selection process is depicted in Figure 1.…”
Section: Baseline Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The study selection process is depicted in Figure 1. Among those including articles, 13 studies only reported associated factors for development of CVC, while the other 9 (15)(16)(17)(18)(38)(39)(40)(41)(42) studies also explored the association of CVC and mortality meanwhile. Patients treated with hemodialysis were enrolled in 9 studies, while patients treated with peritoneal dialysis were enrolled in 6 studies.…”
Section: Baseline Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The C-STRIDE study analyses showed that AAC may be associated with the risk of death for patients with CKD of any severity, while CVC is a possible risk factor for cardiovascular disease but only among those patients with mild to moderate CKD in the Chinese cohort [ 25 ]. Our previous study found that CVC increased the risk of all-cause and cardiovascular mortality among HD patients [ 26 ]. We sought to investigate the contributions of AAC and CVC to adverse events by using the partial chi-square statistic minus the predictor degrees of freedom [ 27 ].…”
Section: Discussionmentioning
confidence: 99%